2020
DOI: 10.3386/w27494
|View full text |Cite
|
Sign up to set email alerts
|

Older People are Less Pessimistic about the Health Risks of Covid-19

Abstract: We thank Daniele d'Arienzo for excellent research assistance. Coffman thanks Harvard Business School for their financial support. Gennaioli thanks the European Research Council for financial support. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
33
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 11 publications
9
33
3
2
Order By: Relevance
“…4 This may be related to differences in perception of COVID-19 risk among rural residents, who did not initially perceive their risk to be high. 16 This may also be related to the fact that major metropolitan areas were the first impacted by COVID-19, which may have informed public perception that the spread of COVID-19 was primarily an urban problem. 17 In this case, rural populations may not have adopted preventive behaviors, such as social distancing or facemasking, as early as their metropolitan counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 This may be related to differences in perception of COVID-19 risk among rural residents, who did not initially perceive their risk to be high. 16 This may also be related to the fact that major metropolitan areas were the first impacted by COVID-19, which may have informed public perception that the spread of COVID-19 was primarily an urban problem. 17 In this case, rural populations may not have adopted preventive behaviors, such as social distancing or facemasking, as early as their metropolitan counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the rising rates in nonmetropolitan America is that rural communities may have missed some opportunities to contain the spread of COVID‐19 despite factors, such as low population density and limited travel to and from rural locations, which could have resulted in less opportunity for COVID‐19 exposure 4 . This may be related to differences in perception of COVID‐19 risk among rural residents, who did not initially perceive their risk to be high 16 . This may also be related to the fact that major metropolitan areas were the first impacted by COVID‐19, which may have informed public perception that the spread of COVID‐19 was primarily an urban problem 17 .…”
Section: Discussionmentioning
confidence: 99%
“…17 Other studies have shown mixed results by age, with some reporting higher risk perceptions for older adults 18 and others lower. 19 Our study showed that older respondents were more likely to view social gatherings with many people and indoor activities as unsafe, yet more likely to view activities such as going to the grocery store, participating in outdoor activities, visiting elderly relatives, and visiting the doctor or emergency room as safe.…”
Section: Discussionmentioning
confidence: 59%
“…As of January 2021, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes coronavirus disease (COVID- 19), has infected more than 23 million people and contributed to over 390,000 deaths in the United States. 1 The negative health and social consequences of the COVID-19 pandemic -including morbidity and mortality; decreased access to health care; and lost jobs and economic hardships -have not been experienced equally, and instead have impacted certain communities in greater numbers and with increased severity.…”
Section: Introductionmentioning
confidence: 99%
“…However, perhaps surprisingly, survey research has shown that older Americans tend to be less pessimistic about COVID-19 health risks(Bordalo et al 2020).…”
mentioning
confidence: 99%